Library Instruction Ideas for Science and Technology: A Baker's Dozen - Angie Locknar; Grace Baysinger; Rosemary L. Meszaros (Issues in Science and Technology Librarianship, 1997)
Authors provide a list of 13 suggestions for improving your library instruction.